A Clinical, Radiographic and Histological Study of Unerupted Teeth in Dogs and Cats: 73 Cases (2001–2018) - Bellei, Emma; Ferro, Silvia; Zini, Eric; Gracis, Margherita (Frontiers in Veterinary Science, 2019)
Lack of dental eruption may be accompanied by development of dentigerous cysts and has also been rarely associated with neoplasia. However, little information is available on prevalence of unerupted teeth and associated lesions in dogs and cats. The main objective of this study was to describe the epidemiologic data of canine and feline dental patients with unerupted teeth, and assess the prevalence of associated dentigerous cysts and tumors. Secondary aims included the evaluation of possible factors implicated in cystic development, and description of the histological features of dentigerous cysts. Medical and dental records, intraoral photographs, intraoral radiographs of client-owned dogs and cats with clinically missing teeth examined between 2001 and March 2018 were reviewed. Collected data included signalment, reason for presentation, number, type, depth of inclusion and angulation of unerupted teeth, presence of cystic lesions or tumors, abnormalities affecting involved teeth, histopathological findings, performed treatment and outcome. Seventy-three animals (69 dogs and 4 cats) with 113 unerupted teeth were included. The most frequent unerupted tooth in dogs was the first premolar teeth (78%), followed by the canine and third molar teeth. Dentigerous cysts were diagnosed associated with 48 (44.4%) teeth in dogs and one out of five unerupted teeth in cats. The affected teeth in dogs were predominantly in horizontal inclination (40%) and in soft tissue inclusion (77%). Brachycephalic canine breeds were overrepresented. The only unerupted tooth in boxer dogs was the first premolar tooth (32 teeth). Ninety percentage of boxers with unerupted teeth developed associated lesions (25 dentigerous cysts and one tumor). Two ameloblastomas (one in a dog and one in a cat) and one osteosarcoma (in a dog) were diagnosed in association with three unerupted teeth. Histology was essential in diagnosing two odontogenic cysts not evident on radiographs. In all cases that were followed-up, treatment (i.e., extraction, extraction and surgical curettage, or operculectomy) appeared successful. Untreated dentigerous cysts showed progression at re-examination. None of the unerupted teeth without evidence of cyst at the time of diagnosis showed incipient cystic development. None of the evaluated factors were associated with lack of eruption and/or development of associated lesions.